B2C-oriented quality control of logistics services based on an economic perspective - Orozonova, Azyk; Akmatova, Aigerim (Advanced Logistic Systems - Theory and Practice, 2024)
The research of the quality control of logistics services relevancy is determined by the increasingly dynamic and competitive nature of the market requires companies to ensure the high quality of their logistics services, especially in the sphere of business-to-consumer (B2C). The research aims to analyse and identify optimal approaches and strategies for quality control of logistics services in B2C interactions. Among the methods used were the analytical method, statistical method, functional method, system analysis method, deduction method, synthesis method and comparison method. In the process of the study, the current practice of quality control in B2C logistics was analysed. An economic relevance assessment identified how service quality can affect business and also assessed the potential benefits of improving it. Approaches to quality control were analysed, including such methods as statistical data analysis, internal and external audits, application of quality standards, and use of technology for monitoring and tracking processes. Opportunities to optimise logistics processes and their impact on overall quality were also considered. A comparative analysis of practices in the industry identified best practices and innovations. The study summarised current trends and provided practical recommendations for companies seeking to optimise quality control of logistics services on a cost-effective basis. The practical relevance of the findings is to provide companies with valuable tools and insights to improve their logistics operations and enhance customer service.